Bilirubin improves renal function by reversing the endoplasmic reticulum stress and inflammation in the kidneys of type 2 diabetic rats fed high-fat diet. (1st June 2023) - Maleki, Mohammad Hassan; Nadimi, Elham; Vakili, Omid; Tavakoli, Ramin; Taghizadeh, Motahareh; Dehghanian, Amirreza; Bordbar, Hossein; Shafiee, Sayed Mohammad
Abstract: Diabetic kidney disease (DKD), as a chronic diabetes-induced complication, is considered the most frequent leading cause of end-stage renal disease (ESRD). Regarding the observed protective effects of bilirubin, as a potential endogenous antioxidant/anti-inflammatory compound, against DKD progression, we planned to evaluate the effects of bilirubin administration on endoplasmic reticulum (ER) stress and inflammation in type 2 diabetic (T2D) rats fed high-fat diet (HFD). In this regard, thirty 8-week adult male Sprague Dawley rats were divided into five groups (n = 6). T2D and obesity were induced by streptozotocin (STZ) (35 mg/kg) and HFD (700 kcal/day), respectively. Bilirubin treatment was carried out for 6- and 14-week intervals (10 mg/kg/day), intraperitoneally. Then, the expression levels of ER stress-related genes (i.e. binding immunoglobulin protein ( Bip ), C/EBP homologous protein ( Chop ), and spliced x-box-binding protein 1 ( sXbp1 ), as well as nuclear factor-κB (NF-κB) were analyzed using quantitative Real-time PCR experiments. Moreover, histopathological and stereological changes of kidney and its related structures were investigated for the studied rats. Bip, Chop, and NF-κB expression levels were significantly decreased under bilirubin treatment, while sXbp1 was up-regulated following the bilirubin administration. More interestingly, glomerular constructive damages seen in HFD-T2D rats, were considerably improved in the animals received bilirubin. Stereological assessments also revealed that bilirubin could desirably reverse the mitigation of kidney's total volume and its related structures, such as cortex, glomeruli, and convoluted tubules. Taken together, bilirubin has potential protective/ameliorative effects on DKD progression, especially through alleviating the renal ER stress and inflammatory responses in T2D rats with injured kidneys. In this era, clinical benefits of mild hyperbilirubinemia can be considered in human DKD. Highlights: An inverse correlation exists between bilirubin and diabetic kidney disease in rats. Bilirubin can potentially reverse the endoplasmic reticulum stress and inflammation. In diabetic kidneys, glomerular constructive damages are ameliorated by bilirubin. The shrinkage of renal tissue can also be reversed in the presence of bilirubin.